Lacey, Wells and Quick Reconstructing criminal law : text and materials / Celia Wells, Oliver Quick. - Wells, Celia; Quick, Oliver; Lacey, Nicola (Law in Context., 2010)
Since the publication of the first edition, this textbook has offered one of the most distinctive and innovative approaches to the study of criminal law. Looking at both traditional and emerging areas, such as public order offences and corporate manslaughter, it offers a broad and thorough perspective on the subject. Material is organised thematically and is clearly signposted at the beginning of each section to allow the student to navigate successfully through the different fields. This fourth edition looks at topical issues such as policing, the Serious Crime Act 2007, and reform of the Fraud Act 2006. Relevant case law and extracts from the most topical and engaging debates on the subject give the subject immediacy. The book is essential for both undergraduate and postgraduate study of criminal law and justice.